IMPLEMENTASI METODE PEMBELAJARAN BERBALIK (RESIPROCAL TEACHING) PADA MATA PELAJARAN AKUNTANSI - Haryati, J Titik (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objective of the researches is to know wether resiprocal teaching learning can improve understanding accounting subject on the topic transaction journal cooperative accounting. Population in this research where XII IPS students in SMA Negeri 1 Tegal. Sample in this research where XII IPS 1 students in SMA Negeri 1 Tegal. Result of this research show reciprocal teaching learning implementation can improve understanding accounting subject on the topic transaction journal cooperative accounting. This can be should 80% students can reach the target. Based on the result, it is suggested that teacher can implement reciprocal teaching learning, and to use relevan literature. Key Words: Metode pembelajaran berbalik (reciprocal teaching), prestasi belajar